A dependence of a sports result on physical development, morphofunctional and special strength preparedness data of weightlifters at the stage of preliminary basic training - Півень, Олександр; Дорофєєва, Тетяна (Slobozhanskyi Herald of Science and Sport, 2017)
Oleksandr Piven & Tetiana Dorofieieva Purpose: establishing the nature of the relationship between the sporting result of weightlifters 15–17 years and the level of their special physical and morphofunctional preparedness at the stage of preliminary basic training. Material & Methods: 30 athletes of the group of preliminary basic training of the second year of training were involved in the experiment. The study was conducted on the basis of the department of weightlifting and boxing of the Kharkov State Academy of Physical Culture and Children's Sports School "KhTP". Result: correlation between the parameters of the morphofunctional, speed-power and special (competitive) readiness of weightlifters of preliminary basic training are identified. The conducted research shows that the result of competitive exercises of athletes specializing in weightlifting, at the stage of preliminary basic training depends on the strength and speed-strength preparedness. Conclusion: it is established that the correlation between the results of competitive exercises and standing high jump, standing long jump, running at